The timing of Drosophila salivary gland apoptosis displays an l(2)gl -dose response - Farkas, Robert; Mechler, Bernard (Cell death and differentiation, 2000)
During Drosophila metamorphosis, larval tissues, such as the salivary glands, are histolysed whereas imaginal tissues differentiate into adult structures forming at eclosion a fly-shaped adult. Inactivation of the lethal(2)giant larvae (l(2)gl) gene encoding the cytoskeletal associated p127 protein, causes malignant transformation of brain neuroblasts and imaginal disc cells with developmental arrest at the larval-pupal transition phase. At this stage, p127 is expressed in wild-type salivary glands which become fully histolysed 12-13 h after pupariation. By contrast to wild-type, administration of 20-hydroxyecdsone to l(2)gl-deficient salivary glands is unable to induce histolysis, although it releases stored glue granules and gives rise to a nearly normal pupariation chromosome puffing, indicating that p127 is required for salivary gland apoptosis. To unravel the l(2)gl function in this tissue we used transgenic lines expressing reduced (∼0.1) or increased levels of p127 (3.0). Here we show that the timing of salivary gland histolysis displays an l(2)gl-dose response. Reduced p127 expression delays histolysis whereas overexpression accelerates this process without affecting the duration of third larval instar, prepupal and pupal development. Similar l(2)gl-dependence is noticed in the timing of expression of the cell death genes reaper, head involution defective and grim, supporting the idea that p127 plays a critical role in the implementation of ecdysone-triggered apoptosis. These experiments show also that the timing of salivary gland apoptosis can be manipulated without affecting normal development and provide ways to investigate the nature of the components specifically involved in the apoptotic pathway of the salivary glands.